(untitled) (Politeja, 2026)
The article analyzes the contemporary aspects of discursive transit that the Russian regime performs in the context of the need to legitimate its war effort during the crisis of domestic media. This paper attempts to study the problem of which patterns of the discourse of hostility the Russian regime seeks to transfer into Western media discourse on the Russian war in Ukraine to legitimize it. The study of the interview of Vladimir Putin with Tucker Carlson was performed using discourse analysis methods. The interview was studied as an example of the discursive transit of the Russian wartime hostility discourse into the Western media sphere to gain sympathy and legitimize the war course. This problem is relevant in the context of contemporary qualitative political communication research, in understanding the core ideas that the Russian wartime discourse built. This moment is especially interesting in light of the EU-Ukraine cooperation and the constant development of the EU legislation in media regulation and security.